Parents and Students Attitudes towards Learning Arabic Language in Lagos West Senatorial District Nigeria - Mubin Olatoye Raji (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
Arabic language education occupies a unique place in Nigeria, particularly in Lagos West Senatorial District, where cultural diversity and religious plurality shape educational choices. As a language with deep religious, cultural, and economic significance for Muslims, Arabic remains both a spiritual and practical asset. However, parents’ and students’ attitudes significantly influence its uptake in formal schooling. This study aims to investigate the perceptions, motivations, and barriers surrounding Arabic learning among junior secondary school students and their parents in Lagos West, with the broader goal of informing educational policy and planning. Adopting a descriptive survey design, the study combined quantitative and qualitative approaches. A stratified random sample of 150 junior secondary students was drawn from Education Districts 5 and 6, while parents were engaged through structured interviews. Data were collected using a researcher-developed questionnaire, analyzed with descriptive statistics (frequency, percentage, and mean ratings), and tested with inferential methods including t-tests and ANOVA at the 0.05 significance level. Findings indicate that students generally value Arabic for its role in religious development and career opportunities, while parental attitudes are more ambivalent, often influenced by competing educational priorities and varying perceptions of Arabic’s socio-economic relevance. The study concludes by highlighting the need for culturally sensitive policies and targeted awareness strategies to strengthen Arabic language education in Lagos West Senatorial District